The Improvement of TNF- Î± and Inflamation Cell on the Lungs Hypersensitivity Reaction becauses of Wood Dust Exposure - Marufi, Isa; Prahastuti, Anita Dewi; Hartanti, Ragil Ismi (Health Notions, 2018)
This research aimed to analyze the effect of wood dust on TNF-Î± on Mice blood (MusMusculus) BALB / C and to analyze the influence of wood dust on the number of inflammatory cells, ie macrophage, lymphocyte, neutrophil and mast cell in lung tissue of mice BALB / C, as well as explain the mechanism of lungs hypersensitivity reaction due to wood furniture dust exposure. The experimental laboratory research was conducted, and mice was become the animal experiment. The research design used was Randomized the post-test only control group design. Exposure was performed 4 hours a day with 2 hours length of exposure in the morning with 1 hour rest period in 6 times a week for 4 weeks at exposure space in a glass-shaped cube with a size of 20x20x20 cm3. Concentrations of wood furniture dust exposed were 0.50 mg / m3, 0.75 mg / m3, 1.00 mg / m3. The findings showed that: (1) wood furniture dust exposure increased between experimental group compared with control group in mice (Musmusculus) BALB / C; (2) wood furniture dust exposure increased TNF, in lung tissue between experimental group compared with control group in mice (Musmusculus) BALB / C; and (3) wood furniture dust exposure increased mast cells, neutrophils, lymphocytes, and macrophages in lung tissue between experimental group compared with control group in mice (Musmusculus) BALB / C.